Tunnel Structure Kx≈0.25IrO2 Catalyst Anchored on Three-Dimensional Ti Foam as an Efficient Anode for Sulpiride Degradation. (1st September 2017) - Sun, Wei; Zaman, Waqas Qamar; Cao, Li-Mei; Yang, Ji
Graphical abstract: Highlights: Kx≈0.25 IrO2 (h-Ir) is a novel catalyst to degrade sulpiride. First to assemble catalyst to three dimensional structure Ti foam. h-Ir can effectively reduce the overall energy consumption. Abstract: The electrochemical oxidation processes have been proven as an efficient and environment-friendly techniques to degrade the organic contaminants. However, higher energy consumption and lower efficiency restrict the commercial applications on large scale. The conventional viewpoint to design anodes for the electrochemical degradation applications is to avoid the OER occurrence. However, the OER not only plays a positive role in preventing anodic fouling, but also produces various activated oxygen species (O*, OH* and OOH*) to benefit oxidation of organic pollutants. Here, we demonstrate that a novel catalyst Kx≈0.25 IrO2 has a unique tunnel structure and d bands, when fixed on Ti foam to form a three dimensional (3D) architecture anode, can efficiently degrade the sulpiride both in acidic and neutral solution. It can achieve 61% mineralization in acidic environment, which is five times higher than that of IrO2 under the same condition and two times higher than that of performed Fenton degradation. This 3D architecture not only provides a large surface area but also escalates the mass transfer, which is a crucial factor for the SP degradation. In short, we demonstrate that the tunnel structure catalyst along with high OER activity not only provides an attractive degradation performance, but can reduce the cell potential to decrease the energy consumption.